Inflammatory Pseudotumor of the Kidney - Onur, Mehmet Ruhi; Firdolas, Fatih; Kocakoc, Ercan; Orhan, Irfan (Medknow Publications & Media Pvt Ltd, 2011)
Inflammatory pseudotumor of the kidney is a rare benign condition with unknown etiology that can mimic malignancy. We report a case of inflammatory pseudotumor of the kidney. A 59-year-old male patient was admitted with a complaint of right flank pain and hematuria. Ultrasonography and magnetic resonance imaging of the patient revealed a 9 cm x 10 cm mass originating from the renal parenchyma with posterior extension. Operative findings revealed a mass adhering to the psoas muscle. Histopathologic examination demonstrated spindle-shaped fibroblast cells accompanying inflammatory cells. The pathological diagnosis was renal inflammatory pseudotumor. Repeated US and computed tomography revealed complete remission.
Keywords: Inflammatory pseudotumor; kidney; magnetic resonance imaging; ultrasonography